Severity of Seizures and Anxiety among People with Epilepsy: A Case Study from India - Pandey, Subodh (Issues and Developments in Medicine and Medical Research Vol. 4, 2022)
The purpose of this study was to determine and correlate level severity of seizure with anxiety scores of people with epilepsy. The anxiety in epileptic patients can manifest during either as an aura, ictal, inter-ictal or postictal episodes. Forty-five epileptic patients were included in the study. The patients were clinically diagnosed for epilepsy and confirmed electroencephalographically and suffering at least with epilepsy for two years were included in the study. This study provides the evidence that there is an association between seizure severity and anxiety scores of epileptic patients, thus suggesting that severity of seizures may have a role in the genesis of anxiety in epileptic patients. It is concluded that seizure severity can have an impact in the genesis of anxiety and it might be possible that if measures are taken to reduce the severity of seizure the associated anxiety can be attenuated and will improve the quality of life of people with epilepsy.